Socioeconomic inequalities in health and nutrition among older adults in Mexico - Aarón Salinas-Rodríguez; Betty Manrique-Espinoza; Vanessa De la Cruz-Góngora; Ana Rivera-Almaraz (Instituto Nacional de Salud Pública, 2019)
Objective. To analyze the socioeconomic inequalities in health among the population of older adults in Mexico. Materials and methods. Analysis of two national health surveys in Mexico (Ensanut 2012 and Ensanut 100k) in which inequality gradients are estimated for various health and nutrition outcomes of older adults over 60 years, using the Relative Index of Inequality (RII) and the Slope Index of Inequality (SII). Results. Older adults with lower socioeconomic status had worse levels of cognition, instrumental activities of daily living, depressive symptoms, muscle mass, low weight, and anemia. Conclusions. Substantial socioeconomic inequalities in health were observed in this study. Given the rapid growth of the population of older adults in Mexico, our results indicate that urgent actions are necessary to achieve health equity in this population group, particularly universal access to health, as well as universal coverage of health services.